2, 6‐Diphospha‐s‐indacene‐1, 3, 5, 7(2 H, 6 H)‐tetraone: A Phosphorus Analogue of Aromatic Diimides with the Minimal Core Exhibiting High Electron‐Accepting Ability. Issue 33 (17th July 2014) - Takeda, Youhei; Nishida, Takuya; Minakata, Satoshi
Abstract Phosphorus analogues of pyrromellitic diimides (PyDIs), which represent a family of privileged electron‐accepting organic compounds, have been successfully synthesized as novel electron‐accepting π‐conjugated molecules. Investigation into their physicochemical properties uncovered their prominent electron‐accepting abilities over the corresponding PyDI. Furthermore, theoretical studies revealed the significant contribution of σ*–π* hyperconjugation in stabilizing the LUMO+1.